2019
DOI: 10.1016/j.jaci.2019.01.044
|View full text |Cite
|
Sign up to set email alerts
|

STING-associated lung disease in mice relies on T cells but not type I interferon

Abstract: Background: Monogenic interferonopathies are thought to be mediated by type I interferon. For example, a gain-of-function mutation in stimulator of interferon genes (STING; N153S) upregulates type I interferon-stimulated genes and causes perivascular inflammatory lung disease in mice. The equivalent mutation in human subjects also causes lung disease, which is thought to require signaling through the cyclic GMP-AMP synthase (cGAS)-STING pathway and subsequent activation of interferon regulatory factors (IRFs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
113
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(134 citation statements)
references
References 34 publications
9
113
2
Order By: Relevance
“…Recently it has been shown that during WNV infection causes delayed GI transit, dependent on infiltrating antiviral CD8+ T cells [80]. Furthermore, both in this model and in a lung model where STING exhibits a gain-of-function mutation, T cell-dependent chronic tissue damage occurs, supporting our findings that STING may play a broad and significant role in communicating between the innate and adaptive immune responses [80, 81]. Together, these data demonstrate an essential neuroprotective role for STING during WNV infection, potentially through a cellular mediated mechanism instead of the canonical interferon antiviral function typically attributed to STING.…”
Section: Discussionsupporting
confidence: 85%
“…Recently it has been shown that during WNV infection causes delayed GI transit, dependent on infiltrating antiviral CD8+ T cells [80]. Furthermore, both in this model and in a lung model where STING exhibits a gain-of-function mutation, T cell-dependent chronic tissue damage occurs, supporting our findings that STING may play a broad and significant role in communicating between the innate and adaptive immune responses [80, 81]. Together, these data demonstrate an essential neuroprotective role for STING during WNV infection, potentially through a cellular mediated mechanism instead of the canonical interferon antiviral function typically attributed to STING.…”
Section: Discussionsupporting
confidence: 85%
“…When the STING signal is stimulated, apoptosis occurs more frequently in normal or cancerous T cells (119). Also, bone-marrow chimeras and gene-knockout studies have shown that T cells defect in SAVI are not associated with type-I IFN signaling or cGAS (213,214). Localization of STING at the Golgi can cause delay of T-cell mitosis and reduced proliferation independently of IRF3 and TBK1 (215).…”
Section: Cgas-sting Pathway In Autoimmune or Inflammatory Diseasesmentioning
confidence: 99%
“…Excess of IFN-I ( 31 ) does not contribute to this lymphopenia. Signs of inflammation in lungs and kidneys were also IFN-independent ( 77 ), and probably driven by over-reactivity of the TCR ( 32 , 78 ). This is in line with the observation that in mice STING-associated vasculopathy, STING regulates T cell proliferation in cell culture, independently of IRF3 ( 32 ).…”
Section: Introductionmentioning
confidence: 99%
“…STING mutants also induce chronic activation of ER stress and unfolded protein response (UPR) within T lymphocytes. STING-N154S disrupts calcium homeostasis in T cells, and primes them to become hyper-responsive to T cell receptor signaling induced ER stress, leading to cell death, both in CD4+ and CD8+ T cells ( 32 , 78 ). The mouse CD4+ and CD8+ T cell death through ER stress can be restored (as well as lung disease) by changing TCR specificity ( 36 ).…”
Section: Introductionmentioning
confidence: 99%